2010
DOI: 10.2193/2009-571
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Activity Patterns of Sympatric and Allopatric Black and Grizzly Bears

Abstract: The distribution of grizzly (Ursus arctos) and American black bears (U. americanus) overlaps in western North America. Few studies have detailed activity patterns where the species are sympatric and no studies contrasted patterns where populations are both sympatric and allopatric. We contrasted activity patterns for sympatric black and grizzly bears and for black bears allopatric to grizzly bears, how human influences altered patterns, and rates of grizzly-black bear predation. Activity patterns differed betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 56 publications
4
83
0
Order By: Relevance
“…One explanation is that the reduced HRs exhibited by females were a result of reduced activity in response to human activities. Bears have been observed to limit diurnal foraging activity to avoid competitors (Schwartz et al 2010) or in response to human presence (Ayres et al 1986, Baruch-Mordo et al 2014. Alternatively, what we observed may have been complicated by road crossing.…”
Section: Human Disturbance Effectsmentioning
confidence: 76%
“…One explanation is that the reduced HRs exhibited by females were a result of reduced activity in response to human activities. Bears have been observed to limit diurnal foraging activity to avoid competitors (Schwartz et al 2010) or in response to human presence (Ayres et al 1986, Baruch-Mordo et al 2014. Alternatively, what we observed may have been complicated by road crossing.…”
Section: Human Disturbance Effectsmentioning
confidence: 76%
“…We chose 1-h time units because these were our most finescaled temporal data and hourly readings were possible after 2004 using improved collars that allowed a collar to last 1.5 years at an hourly fix rate during the non-denning period. We only measured movements outside the denning period because previous research has shown that Grizzly Bear movements are reduced before den entry (nelson et al 1983;Friebe et al 2001;Manchi and Swenson 2005) and immediately after den exit (Craighead and Craighead 1972;nelson et al 1983;Schwartz et al 2010). to exclude the denning period, we removed data locations within 500 m of known den sites and within an average of 7 days of den entry and exit dates (see below).…”
Section: Movement Ratesmentioning
confidence: 99%
“…The risks to non-target animals from wider use of the GnRH vaccine are low; a species-specific system for delivery of baits to wild boar has been developed that could prevent uptake of baits by non-target species (Massei et al 2010;Campbell et al 2011), and consumption of meat from GnRH- Table 1. Comparison of regression models by Bayesian information criterion (BIC) scores contrasting differences in temporal patterns of activity and movement between wild boars treated with the immunocontraceptive GonaConÔ and wild boars treated with saline only (controls) Models 1 and 2 fitted means with uncorrelated and correlated errors, respectively, and Models 3 and 4 used radian-transformed hours as independent variables with uncorrelated and correlated errors, respectively (Schwartz Cain et al 2010). The lowest score for Model 1 or 2 indicates no difference in the daily activity or movement cycle, whereas a low score for Model 3 or 4 signifies a difference in the cycle between groups.…”
Section: Discussionmentioning
confidence: 99%
“…To test for differences between the daily patterns of activity and movement for treated and control groups of wild boar each season, the approach used by Schwartz et al (2010) was followed in which four regression models were fitted for each comparison. The response variable was the difference in the mean activity count (z-score) or distance moved between the two groups (treated, control).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation